Development and Assessment of the Stability of Hospital Derivation of Tacrolimus - Venturi, Caroline Rita; Primieri, Gabriele Bordignon; Ayres, Márcio Vinícius; Almeida, Silvia Helena Oliveira de (Drug Analytical Research, 2026)
Tacrolimus is an immunosuppressive drug widely used in hospitals for the treatment of transplant patients. Often, hospitalized patients undergo the administration of tacrolimus in liquid pharmaceutical forms. However, this drug has been marketed only in solid form for oral use. This work aimed to develop and evaluate the stability of tacrolimus in a simple liquid formulation with comparable efficacy, safety, and stability. The analyzes were developed according to the USP method (2018), being co-validated, guaranteeing its accuracy, precision, and specificity. Based on the analyzed analyses, the derivation of tacrolimus in suspension was determined, as well as the wetting agent in its ideal proportion to obtain drug content in HPLC within acceptable limits, this being 8% polyethylene glycol 400. The formulation was observed for the evaluation of physical-chemical parameters, being grown, pH, sedimentation volume, and organoleptic characteristics. Dosing was carried out for 30 days at room temperature and a temperature of 40°C. The formulation maintained its integrity during the 30 days of storage at room temperature with content between 90 – 110%, growth above 200 cP, neutral pH, and sedimentation volume below 3 mL. However, tacrolimus is controlled sensitively to heat, observing degradation in the first ten days of analysis at 40°C, with possible formation of degradation products. Based on this work, the tacrolimus formulation developed has adequate dosage and homogeneity for 30 days and should be kept away from light and at room temperature.